Information technology and employees performance: A case of fingerprint unit at Tanzania police force - Siwale, Violeth M (Mzumbe University, 2024)
A research paper submitted to Mzumbe University in partial fulfillment of the requirements for the Degree of Master of Science in Human Resource Management (MSc-HRM) of Mzumbe University